Endogenous Retroviruses (ERVs): Does RLR (RIG-I-Like Receptors)-MAVS Pathway Directly Control Senescence and Aging as a Consequence of ERV De-Repression? - Di Giorgio, Eros; Xodo, Luigi E. (Frontiers in Immunology, 2022)
Bi-directional transcription of Human Endogenous Retroviruses (hERVs) is a common feature of autoimmunity, neurodegeneration and cancer. Higher rates of cancer incidence, neurodegeneration and autoimmunity but a lower prevalence of autoimmune diseases characterize elderly people. Although the re-expression of hERVs is commonly observed in different cellular models of senescence as a result of the loss of their epigenetic transcriptional silencing, the hERVs modulation during aging is more complex, with a peak of activation in the sixties and a decline in the nineties. What is clearly accepted, instead, is the impact of the re-activation of dormant hERV on the maintenance of stemness and tissue self-renewing properties. An innate cellular immunity system, based on the RLR-MAVS circuit, controls the degradation of dsRNAs arising from the transcription of hERV elements, similarly to what happens for the accumulation of cytoplasmic DNA leading to the activation of cGAS/STING pathway. While agonists and inhibitors of the cGAS–STING pathway are considered promising immunomodulatory molecules, the effect of the RLR-MAVS pathway on innate immunity is still largely based on correlations and not on causality. Here we review the most recent evidence regarding the activation of MDA5-RIG1-MAVS pathway as a result of hERV de-repression during aging, immunosenescence, cancer and autoimmunity. We will also deal with the epigenetic mechanisms controlling hERV repression and with the strategies that can be adopted to modulate hERV expression in a therapeutic perspective. Finally, we will discuss if the RLR-MAVS signalling pathway actively modulates physiological and pathological conditions or if it is passively activated by them.